PERBEDAAN KEPADATAN LALAT YANG HINGGAP PADA FLY GRILL YANG BERBEDA WARNA DI PAJAK SINGA KOTA KABANJAHE KABUPATEN KARO TAHUN 2018 - Erba Kalto Manik; Susanti br Perangin-Angin (Poltekkes Kemenkes Medan, 2019)
Flies are Arthropoda insects that belong to the order of Diptera. Flies can transmit the disease through allthe limbs such as feces, vomit, body hair, limb hair and especially on the legs that have fine hairs so that theseeds of the disease can stick. Flies have a life activity interacting with a place that is a habitat for diseasessuch as trash, feces and carcasses. Plus its ability to fly 1-2 miles of several species of flies can spreadseveral diseases such as Thgypoid Fever, Parathypoid, bacillary dysentery, amoebic dysentery, and severaleye diseases from various places that have been visited. Flies are insects in general having sensitivity todifferent light wavelengths (colors). This research is a field experiment and includes a Pre Experiment that isPostest Only Design which aims to analyze differences in the density of flies that land on Fly Grill which aredifferent colors in Singa Kabanjahe Tax to plan control efforts which are about when, where and howcontrol will be carried out. in the Singa Kabanjahe Tax TPS for 10 days and the number of flies perched withdifferent fly grill colors (orange, pink, light blue, light green and yellow) for 30 seconds, calculating 10 timesthe calculation with the highest average. The data obtained were analyzed by ANOVA test with an error rateof 0.05. From the ANOVA test data with = 0.05 shows p = 0.221, which means that there is no difference indensity of flies perched on a different color fly grill. The average density of flies, from the lowest to thehighest is as follows: fly grill in orange, light green, light blue, pink and yellow ... The conclusion that can bedrawn is that flies do not like orange, light green and light blue. Meanwhile, the color favored by flies isyellow